Post-coronavirus disease 2019 functional impairments, limitations, and restrictions: A prospective cohort study based on the international classification of functioning, disability, and health - Monteiro, Isabella Polo; Appelt, Pablo Andrei; Sisconetto, Angélica Taciana; Minaré Baldo Sucupira, Kelly Savana; Bazan, Rodrigo [UNESP]; Luvizutto, Gustavo José; Pascucci Sande de Souza, Luciane Aparecida (SAGE Publications, 2023)
Background: Current knowledge regarding coronavirus disease 2019 (COVID-19) is constantly evolving, and the long-term functional impairments, limitations, and restrictions have not yet been well established. Objective: to evaluate the impact of post-COVID condition on the human functioning through the International Classification of Functioning, Disability and Health (ICF) classification. Methods: This is a prospective cohort study with 53 individuals with post-COVID condition at 3 time points: 0 to 3 (baseline), 3 to 6, and 6-12 months (follow-up). Outcomes were organized in dichotomous variable: No impairment (0); presence of impairment (≥1) in body function, structure, activities, and participation domains according to the ICF checklist. Chi-square test was used to determine the differences of 3 time points, and association with persistent symptoms. Results: A statistically significant difference was observed between the periods, with greater disabilities at 6-12 than at 0-3 months in mental, sensory, pain, and movement-related functions; cardiovascular, immunological, and respiratory systems. In terms of activity and participation, a greater limitation at 6-12 months was observed than at 0-3 months in learning and applying knowledge, general tasks, and mobility. In the domain of interpersonal interactions and relationships, there was a statistically significant difference between the 6-12 and 3-6 months groups. Associations between COVID-19 symptoms and ICF components at the first follow-up were: anosmia and dysgeusia with weight maintenance, fatigue and irritability with pain, brain fog with watching and listening, walking difficulty with pain, and headache with pain, watching, and listening. At the second follow-up were: anosmia and dysgeusia with energy and drive functions, attention, memory, and emotional functions; dizziness with watching and listening; fatigue with emotional function, pain, undertaking multiple tasks, lifting and carrying objects, and driving; irritability with energy and drive, emotional function, undertaking multiple tasks, lifting and carrying objects, and walking; walking difficulty with energy and driving, emotional function, respiration, muscle power, cardiovascular system, undertaking multiple tasks, lifting and carrying objects, and walking; and headache with emotional function, watching, and listening. Conclusions: Individuals with COVID-19 persistent symptoms showed impairments in structure and function, activity limitations, and participation restrictions during the 1-year follow-up period.
Keywords: activity limitations; body function; COVID-19; disability and health; International classification of functioning; participation restrictions